PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Toko Bangunan Sumber Manis Kaliwungu Kendal) - Farid Ali Mustafa, 08.05.51.0078; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2012)
The purpose of this study was to analyze the Effect of variable Product, Price and Promotion on purchase decisions" to the purpose of analyzing purchasing decisions on Building Shop Sumber Manis Kaliwungu Kendal. The population in this study is consumers TB. Sumber Manis Kaliwungu Kendal. Sampling was done by using "purposive sampling" technique of determining if the information for the data samples taken from specific targets, by taking samples with specific criteria. The criterion is consumer TB. Sumber Manis who purchase two or more than two times and the number of samples taken as many as 100 people. The results of this research are: (1) The results of the statistical linear regression analysis can be shown by the regression equation Y = 0.201 X1 + 0.437 X2 + 0.278 X3. From the regression equation it is known that the product, price and promotion has a positive and significant impact on purchasing decisions. (2) The calculation of the coefficient of determination 0.544 magnitude. This means that the effect of the variable product (X1), price (X2) and Promotion (X3), jointly influence the purchase decision variable (Y) equal to 54.4% while the remaining 45.6% is influenced by other variables not included in this study. (3) The hypothesis that has been done in this study are: a) There is a positive and significant relationship between product purchase decisions on TB. Sumber Manis. b) There is a positive and significant correlation between the price of the purchase decisions on TB. Sumber Manis. c) There is a positive and significant relationship between promotion against purchasing decisions on TB. Sumber Manis.Keywords: Product, Price, Promotion and Purchasing Decisions.